2021
DOI: 10.26603/001c.18710
|View full text |Cite
|
Sign up to set email alerts
|

Patients Walking Faster After Anterior Cruciate Ligament Reconstruction Have More Gait Asymmetry

Abstract: Background BackgroundGait asymmetries after anterior cruciate ligament reconstruction (ACLR) may lead to radiographic knee osteoarthritis. Slower walking speeds have been associated with biomarkers suggesting cartilage breakdown. The relationship between walking speed and gait symmetry after ACLR is unknown. Hypothesis/Purpose Hypothesis/PurposeTo determine the relationship between self-selected walking speeds and gait symmetry in athletes after primary, unilateral ACLR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Participants were asked to walk across a 10-m walkway over a built-in force plate (Bertec Corporation, Columbus, OH), at self-selected gait speeds (Table 1). Trials recorded at speeds within 5% of their self-selected gait speeds (9,10,13,25,26) were included for analysis. Retroreflective markers were placed on the pelvis, lower extremity joints, and anatomical landmarks, as described in our previous work (27).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to walk across a 10-m walkway over a built-in force plate (Bertec Corporation, Columbus, OH), at self-selected gait speeds (Table 1). Trials recorded at speeds within 5% of their self-selected gait speeds (9,10,13,25,26) were included for analysis. Retroreflective markers were placed on the pelvis, lower extremity joints, and anatomical landmarks, as described in our previous work (27).…”
Section: Methodsmentioning
confidence: 99%
“…A successful trial was defined as a trial where the participant walked within 5% of their self-selected gait speed with no evidence of targeting or double striking of the force plate. Biomechanics data were collected using an eight-camera system (120 Hz; Vicon, Oxford, UK) and retroreflective markers placed on lower extremity joints and anatomical landmarks (20,21,32,35,38,39). Force plate data were low-pass filtered at 25 Hz, and marker trajectories were low-pass filtered at 6 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The fast speed levels of walking were shown to be a challenging issue for patients with knee diseases. 8 , 9 Previous studies have reported that those who walk fast show more kinetic asymmetries after ACLR, 10 , 11 but the 3D kinematics of ACLR patients at different speeds has not been studied. Recently, we used 3D motion capture to discover the asymmetry of fast walking in patients with ACL deficiency, 12 which led us to wonder if this deficit is fully addressed by ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%